Pengaruh Servicescape Terhadap Repurchase Intention dengan Customer Satisfaction sebagai Variabel Mediasi pada Chili Pade Coffee, Bakery & Eatery Meulaboh Aceh Barat - Nur Rahmi; Ivon Jalil; Rusdi Rusdi (Indo Publishing, 2026)
This study aims to analyze the effect of Servicescape on Repurchase Intention with Customer Satisfaction as a mediating variable among consumers of Chili Pade Coffee, Bakery & Eatery. This research is motivated by the importance of the physical environment in creating Customer Satisfaction and encouraging Repurchase Intention in the culinary industry. The research method used is a quantitative method with an associative approach. Data collection was carried out through questionnaires distributed to 96 respondents who were consumers of Chili Pade Coffee, Bakery & Eatery Meulaboh Aceh Barat. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS 4 software. The results showed that Servicescape had a positive and significant effect on Customer Satisfaction with a t-statistics value of 5.738 and a p-values value of 0.000. Customer Satisfaction also had a positive and significant effect on Repurchase Intention with a t-statistics value of 5.487 and a p-values value of 0.000. In addition, Servicescape had a positive and significant effect on Repurchase Intention with a t-statistics value of 2.324 and a p-values value of 0.020. The mediation test results showed that Customer Satisfaction was able to mediate the effect of Servicescape on Repurchase Intention positively and significantly with a t-statistics value of 3.802 and a p-values value of 0.000. Therefore, the better the Servicescape provided, the higher the Customer Satisfaction and Repurchase Intention of consumers at Chili Pade Coffee, Bakery & Eatery.